2020
DOI: 10.1038/s41467-020-18980-x
|View full text |Cite
|
Sign up to set email alerts
|

CHIP phosphorylation by protein kinase G enhances protein quality control and attenuates cardiac ischemic injury

Abstract: Proteotoxicity from insufficient clearance of misfolded/damaged proteins underlies many diseases. Carboxyl terminus of Hsc70-interacting protein (CHIP) is an important regulator of proteostasis in many cells, having E3-ligase and chaperone functions and often directing damaged proteins towards proteasome recycling. While enhancing CHIP functionality has broad therapeutic potential, prior efforts have all relied on genetic upregulation. Here we report that CHIP-mediated protein turnover is markedly post-transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Therefore, the identification of negative upstream regulators of FoxO1 such as STUB1 might result in valuable therapeutic targets to diminish FoxO1 activation and its negative metabolic consequences. Indeed, strategies aiming to enhance STUB1 functionality for therapeutic applications in cardiovascular disease have been proposed recently 43 , supporting the potential feasibility of targeting STUB1 for clinical gain.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the identification of negative upstream regulators of FoxO1 such as STUB1 might result in valuable therapeutic targets to diminish FoxO1 activation and its negative metabolic consequences. Indeed, strategies aiming to enhance STUB1 functionality for therapeutic applications in cardiovascular disease have been proposed recently 43 , supporting the potential feasibility of targeting STUB1 for clinical gain.…”
Section: Discussionmentioning
confidence: 91%
“…In combination with its chaperone partners, CHIP targets substrates for degradation via proteasomal degradation [ 59 ]. The phosphorylation of CHIP by Protein Kinase G has also recently been shown to increase the activity of the E3 ligase by enhancing its association with chaperones [ 60 ]. CHIP does not exclusively tag proteins for destruction however, it also coordinates misfolded protein aggregation in concert with its chaperone partners upon proteasome inhibition, although this may be an indirect effect [ 61 ].…”
Section: Ubiquitination and Chaperonesmentioning
confidence: 99%
“…87 A recent study of posttranslational modifications of CHIP identified that serine phosphorylation of CHIP also serves to stabilize the interactions between CHIP and Hsp70 and positively influences CHIP-mediated ubiquitination and subsequent proteasomal degradation. 88…”
Section: Hsp70 and Co-chaperones Directing The Protein Quality Control Processmentioning
confidence: 99%